Understanding Metrics For Communicating The Economic Importance of Florida's Fisheries Part III: Measuring Economic Value - Andrew Ropicki; Edward V. Camp; Christa D. Court; Robert Botta (EDIS)
Understanding the economic importance of fisheries and coastal resources is vitally important for making good management decisions that affect human communities, local businesses, and environmental and ecological sustainability. This final publication in a series of three follows Part I, an overview, and Part II, methods to quantify economic activity. Part III focuses on measures of economic value and discusses different ways to think about and estimate the economic values of Florida’s fisheries and aquatic resources.